Extensão universitária e trabalho voluntário na formação do acadêmico em odontologia - Pereira, Stela Márcia; Mialhe, Fábio Luiz; Pereira, Luciano José; Soares, Márcia de Fátima; Tagliaferro, Elaine Pereira da Silva [UNESP]; Meneghim, Marcelo de Castro; Pereira, Antonio Carlos (My University, 2011)
The aim of the present study was to point out the importance of the experience of undergraduate dental students in extra-curricular activities and volunteer work, as a means through which to gain essential knowledge and abilities for their professional lives. A literature review of the Medline, Scielo, and Lilacs databases was carried out in an attempt to select articles related to the university extension and volunteer work of undergraduate dental students. It is still extremely difficult to include university extension and volunteer work as an important activity in Dentistry courses. However, the presentday work market demands professionals who have expertise not only in dental techniques, but also in the socio-cultural characteristics of communities, considering that people need to be comprehensive in their psychosocial aspects in order to be treated as a complete professional. Therefore, university dentistry courses should give equal consideration to both oral rehabilitation skills and the promotion of general healthcare, acquired mainly through extracurricular activities, in an attempt to redeem the integral education of the healthcare professional. Moreover, students should pay closer attention to the opportunities offered during their undergraduate courses, as the work market for dentists is becoming more and more competitive. Moreover, the dentist whose professional life is limited to the dental office will most certainly forgo the opportunity to act in other social areas as well as the recognition that comes with such acts.

Este estudo destacou a importância da vivência do acadêmico em odontologia em atividades extramuros e experiências de trabalho voluntário para a aquisição de conhecimentos e habilidades importantes na futura prática profissional. Foi realizada uma revisão bibliográfica nas bases de dados Medline, Scielo e Lilacs, selecionando os artigos relacionados às atividades de extensão e voluntariado desempenhadas pelos alunos de odontologia. A extensão universitária e o serviço voluntário ainda encontram dificuldades, dentro dos cursos de Odontologia, para se estabelecerem como práticas importantes para a formação do aluno. Entretanto, o mercado de trabalho atual exige um profissional com conhecimentos tanto da técnica quanto das características socioculturais da comunidade no desenvolvimento de sua prática odontológica, uma vez que o ser humano necessita ser compreendido nos seus aspectos biopsicosociais para ser tratado de forma integral. Desta forma, os cursos de Odontologia deveriam prestigiar de forma igualitária na formação do aluno, tanto as habilidades reabilitadoras como as de promoção de saúde, adquiridas, em grande parte, em atividades extra-murais, de maneira a resgatar a formação integral do profissional da saúde. Além disso, o acadêmico deve estar atento às oportunidades oferecidas nestes aspectos durante a graduação, já que a odontologia está se tornando mais competitiva, e o cirurgião-dentista que resume sua vida profissional apenas ao seu consultório, perde a chance de fazer-se conhecer e atuar em outros espaços sociais.
University extension and volunteer work in the education of undergraduate dental students
Keywords: Community-Institutional relations; Education higher; Teaching; Learning; Comunidade-Instituição; Educação superior; Ensino; Aprendizagem